Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Pusdiklat Anti Pencucian Uang Dan Pencegahan Pendanaan Terorisme - Devi Maharani; Muhamad Azis Firdaus; Syahrum Agung (CV. ITTC INDONESIA, 2023)
This research discusses how the style of leadership, the work discipline that influences the performance of employees on the Pusdiklat APU PPT in the city of Depok. The aim of this research is to test and analyze the influence of leadership style and work discipline on the performance of employees at the APU PPT Pusdiklat in the city of Depok. The sampling technique uses the quizier technique with the number of 50 respondents who are the Pusdiklat APU PPT staff. The analytical test tool used is SmartPLS v.4 with SEM analysis method. (Structural EquationModeling). The results of this study show that the leadership style has a positive and significant influence on the the staff performance, the working discipline positively and significantly affects the performance of the staff, the style of leadership and the work of the discipline positive and meaningful impact on the staff performance.